Permasalahan Investasi Bodong Berbasis Online di Indonesia - John jotham Terrance; Diana Putong; Arthur Novy Tuwaidan (Civic Education: Media Kajian Pancasila dan Kewarganegaraan, 2022)
In investing, most people will try to make investments such as investing in stocks, property, saving in banks, even forex trading and others because what they know is that there are so many benefits from investing. It turns out that the ease of investing using only mobile devices has a positive but also a negative impact, many parties are taking advantage of this momentum to seek their own profit by creating "false investment" facilities. This study aims to find out what steps the government can take to overcome the problem of online-based investment fraud that occurs in Indonesia. The research method used is juridical and normative with a statutory, conceptual, and literary approach. From the issues raised, it can be concluded: that people must really understand about investing, especially in the field of online investment to prevent online-based investment fraud.